THE APPLICATION OF DIFFERENTIATED LEARNING IN AN EFFORT TO OVERCOME LEARNING DIFFICULTIES IN ISLAMIC RELIGIOUS EDUCATION - Supyandi, Asep; Ripaldi, Aldi; Diana, Aan; Asshdiqi, Ahmad Fajri (Prodi Pendidikan Agama Islam STAI Darul Falah, 2025)
The application of differentiated learning is one of the efforts made by Islamic Religious Education teachers in improving student learning outcomes caused by learning difficulties in Islamic Religious Education subjects that occur in class 4 SDN Cibadak in the 2022-2023 school year semester 1 material 3.13. This research procedure uses Classroom Action Research (PTK), namely planning, research implementation (Application of differentiated learning), evaluation and reflection. Data were obtained from evaluation and observation sheets, then the data were analyzed using quantitative descriptive analysis. The results of the research on 30 students showed that classical completeness in cycle 1 was 70% or 21 students scored above the KKM of 70 and 9 students below the KKM or 30%. In cycle 2, the data obtained was 90% or 27 students who reached the KKM and only 10% or 3 students who had not reached the KKM. Based on the results of this study, it can be concluded that the application of differentiated learning is strongly believed to be able to overcome student learning difficulties in Islamic Religious Education (PAI) subjects in grade 4 SDN Cibadak.